Method for producing recycled positive electrode active material
The method addresses the issue of excessive wastewater generation in recycling positive electrode active materials by using a sequential washing process with liquids of varying alkali metal content, resulting in reduced environmental impact and costs.
Patent Information
- Application Number
- JP2024054013
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2044-03-28
AI Technical Summary
The existing methods for recycling positive electrode active materials from battery waste generate a large amount of wastewater due to multiple water washing steps, which increases environmental burden and treatment costs.
A method involving the use of a mixture containing a positive electrode active material and an activating agent, where the mixture is heated and then washed with a first liquid containing water and an alkali metal compound, followed by a second wash with a liquid having a lower alkali metal content, to recover the recycled positive electrode active material while minimizing wastewater generation.
This method reduces the amount of wastewater produced during the recycling process, thereby decreasing environmental impact and treatment costs while effectively recovering the positive electrode active material.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]
[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.
[0003] For example, Patent Document 1 discloses a method for recovering a positive electrode active material by mixing a positive electrode mixture with an activation treatment agent containing an alkali metal compound, heating the mixture to decompose the binder, and removing the decomposition product and the activation treatment agent with water or the like. This method is cost-effective in that it does not use an organic solvent and directly recovers a positive electrode active material from battery waste. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]
[0005] When recycling the positive electrode active material in the positive electrode mixture, an activation agent containing an alkali metal compound is added to reactivate the positive electrode active material. After the positive electrode active material is reactivated, the mixture containing the positive electrode active material and the activation agent may be washed with water to remove the activation agent. In this case, since it is difficult to remove the activation agent by washing with water once, the washing may be performed multiple times. However, the amount of wastewater generated by washing increases with the number of washings, which increases the burden on the environment and the cost of treating the wastewater.
[0006] Therefore, an object of the present invention is to provide a method for producing a recycled positive electrode active material that can reduce the amount of wastewater generated by washing with water when washing with water is performed multiple times. [Means for solving the problem]
[0007] The present invention includes, for example, the following [1] to [8]. [1] A method for producing a recycled positive electrode active material, comprising the following steps: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) heating the mixture to obtain a heated mixture. (3) contacting the heated mixture with a first liquid containing water and an alkali metal compound, and then obtaining a first solid component and a first liquid component. (4) contacting the first solid component with a second liquid that contains water and has a lower content of alkali metal compounds than the first liquid, and then obtaining a second solid component and a second liquid component. (5) recovering a recycled positive electrode active material from the second solid component [2] The manufacturing method described in [1], wherein the second liquid contains at least a portion of the first liquid component. [3] The manufacturing method described in [1] or [2], wherein the second liquid is smaller than the first liquid. [4] A method for producing a recycled positive electrode active material, comprising the following steps: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) heating the mixture to obtain a heated mixture. (3) contacting the mixture after heating with a first liquid containing water, and then obtaining a first solid component and a first liquid component. (4) contacting the first solid component with a second liquid containing water and at least a portion of the first liquid component, and then obtaining a second solid component and a second liquid component. (5) recovering a recycled positive electrode active material from the second solid component [5] The manufacturing method described in [4], wherein the second liquid is smaller than the first liquid. [6] A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) heating the mixture to obtain a heated mixture. (3) contacting the mixture after heating with a first liquid containing water, and then obtaining a first solid component and a first liquid component. (4) contacting the first solid component with a second liquid that contains water and is less in amount than the first liquid, and then obtaining a second solid component and a second liquid component. (5) recovering a recycled positive electrode active material from the second solid component [7] The method according to any one of [1] to [6], wherein in the step (2), the mixture is heated to a temperature equal to or higher than the melting point of the activation treatment agent. [8] The method according to any one of [1] to [6], wherein in the step (2), the mixture is heated to a temperature lower than the melting start temperature of the activation treatment agent. Effect of the Invention
[0008] According to the present invention, it is possible to provide a method for producing a recycled positive electrode active material that can reduce the amount of wastewater generated by washing with water when washing with water is performed multiple times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Method of manufacturing recycled positive electrode active material) A method for producing a recycled positive electrode active material will be described below.
[0010] [First embodiment] The method for producing a recycled positive electrode active material according to the first embodiment of the present invention includes the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to obtain a heated mixture Step (3): A step of contacting the mixture after heating with a first liquid containing water and an alkali metal compound, and then obtaining a first solid component and a first liquid component. Step (4): contacting the first solid component with a second liquid that contains water and has a lower content of alkali metal compounds than the first liquid, and then obtaining a second solid component and a second liquid component. Step (5): Recovering recycled positive electrode active material from the second solid component
[0011] According to the method for producing a recycled positive electrode active material according to the first embodiment, when washing with water is performed multiple times, it is possible to reduce the amount of wastewater generated by washing with water. In the conventional method for producing a recycled positive electrode active material, after heating a mixture of a positive electrode mixture and an activation treatment agent, the mixture is brought into contact with water to remove alkali metal compounds derived from the activation treatment agent and recover a recycled positive electrode active material, but in order to remove these components, washing with water may be performed multiple times, which may result in the generation of a large amount of wastewater. On the other hand, in the method for producing a recycled positive electrode active material according to the first embodiment, after heating a mixture of a positive electrode mixture and an activation treatment agent, a first liquid containing an alkali metal compound is used as a liquid to be in contact with the mixture. The first liquid may be wastewater generated during the production of a recycled positive electrode active material. Although the wastewater generated during the production of a recycled positive electrode active material contains an alkali metal compound, the alkali metal compound in the wastewater is less than the saturation concentration. Therefore, when the mixture is washed with waste water, alkali metal compounds (especially easily soluble alkali metal compounds such as fluorides of sodium, potassium, etc., and carbonates) derived from the activation treatment agent remaining in the mixture can be dissolved, and it is possible to remove the alkali metal compounds derived from the activation treatment agent in the same way as in the conventional washing method using pure water, etc. Therefore, while the mixture is conventionally washed with pure water, etc., it is possible to use waste water instead of pure water, etc. for washing, thereby reducing the amount of waste water generated during the production of recycled positive electrode active materials.
[0012] Hereinafter, each step in the first embodiment will be described in detail.
[0013] Pre-process (A): Positive electrode composite preparation process A positive electrode mixture containing a positive electrode active material is prepared.
[0014] In the positive electrode mixture, the particles of the positive electrode active material may be bound to each other by a binder. The positive electrode mixture may contain a conductive material and / or an electrolyte in addition to the positive electrode active material and the binder. When the positive electrode mixture contains a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by a binder. The electrolyte is a component that originates from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound that originates from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).
[0015] [Cathode active material] Examples of the positive electrode active material include composite compounds containing one or more of the following elements as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten.
[0016] The positive electrode active material may be composed of only a single compound, or may be composed of a plurality of compounds.
[0017] The positive electrode active material preferably contains a composite oxide containing at least one element selected from element group 1 below and at least one element selected from element group 2 below. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
[0018] The positive electrode active material preferably contains a compound represented by the following formula (A).
[0019] Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements excluding Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metal elements excluding O and P, -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5 are satisfied.
[0020] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X include F, S, Cl, Br, I, Se, Te, N, etc.
[0021] The positive electrode active material preferably contains a composite oxide containing at least Li and Ni.
[0022] In the positive electrode active material, the molar fraction of Ni in M 1 is preferably 0.3 to 0.95.
[0023] The crystal structure of the positive electrode active material (for example, the composite oxide) is not particularly limited, but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is more preferred.
[0024] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0025] The monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0026] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m contained in a hexagonal crystal structure, or the space group C2 / m contained in a monoclinic crystal structure.
[0027] The crystal structure of the positive electrode active material can be identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.
[0028] The particle size of the positive electrode active material in the positive electrode mixture is not particularly limited, but may be about 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments). A volume-based cumulative particle size distribution curve is created from the particle size distribution, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material.
[0029] There is no particular limitation on the content of the positive electrode active material in the positive electrode mixture.
[0030] [Binding agent] Examples of the binder (binder before activation treatment) contained in the positive electrode mixture include thermoplastic resins, and specific examples thereof include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). The binder may be used alone or in combination of two or more kinds.
[0031] The content of the binder in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.
[0032] [Conductive material] Examples of the conductive material include metal-based conductive materials such as metal particles; and carbon-based conductive materials made of carbon materials.
[0033] Specific examples of carbon-based conductive materials include graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers and carbon nanotubes).
[0034] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.
[0035] The specific surface area of the carbon material used as the carbon-based conductive material is 0.1 to 500 m 2 In this case, the conductive material may have a specific surface area of 30 m 2 / g or more, and is made of only carbon-based conductive materials with a specific surface area of 30 m 2 / g or more, and may be carbon black having a specific surface area of 30 m 2 When an activating treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the rate of oxidation treatment of the carbon-based conductive material can be increased, and even a carbon material having a small specific surface area can be oxidized in some cases.
[0036] The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.
[0037] [Electrolytes and Solvents] Examples of the electrolyte include LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, LiCF3SO3, etc. The content of the electrolyte contained in the positive electrode mixture is not particularly limited, but may be 0.0005 to 7 mass %.
[0038] The positive electrode mixture may contain a solvent derived from the electrolyte, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.
[0039] [Recovery of cathode mixture] The positive electrode mixture can be obtained by separating and recovering the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer.
[0040] The "scrap positive electrodes" may be positive electrodes recovered from discarded batteries, and waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. The discarded batteries may be used batteries, or unused but non-standard batteries. The waste positive electrodes may be the ends of positive electrodes generated during the manufacturing process of batteries, or non-standard positive electrodes. As the positive electrode composite, waste positive electrode composite not attached to a current collector (waste generated during the manufacturing process of the positive electrode composite) may also be used.
[0041] The waste positive electrode has a current collector which is a metal foil such as aluminum foil or copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.
[0042] Examples of a method for separating the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer include a method for mechanically peeling the positive electrode mixture layer from the current collector (e.g., a method for scraping the positive electrode mixture layer from the current collector), a method for penetrating a solvent into the interface between the current collector and the positive electrode mixture layer to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.
[0043] Previous process (B): Positive electrode mixture cleaning process Next, when the cathode mixture contains an electrolyte, it is preferable to bring the prepared cathode mixture into contact with an electrolyte washing solvent to remove at least a part of the electrolyte from the cathode mixture. Specifically, the cathode mixture containing the cathode active material, the binder, and the electrolyte is brought into contact with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.
[0044] Solid-liquid separation is an operation for separating a slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.
[0045] The electrolyte cleaning solvent is not particularly limited. Examples of the electrolyte cleaning solvent include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.
[0046] The positive electrode mixture can be brought into contact with the electrolyte washing solvent in a known contact device for powder and liquid (for example, a stirring tank).
[0047] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, it is preferable to obtain a slurry by stirring the positive electrode mixture and the electrolyte washing solvent. The peripheral speed of the tip of the stirring blade may be 0.1 to 1.0 m / s.
[0048] In the washing step of the positive electrode composite material, after solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is again brought into contact with the electrolyte washing solvent to obtain a slurry, and the slurry is again separated into a solid component and a liquid component. In the washing step of the positive electrode composite material, rinsing may be performed multiple times. The slurry concentration in the rinsing can be adjusted as desired. In the rinsing, the slurry can also be stirred as described above.
[0049] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material may change from a layered rock salt structure to a spinel structure. LiPF6+16LiMO2+2O2→ 6LiF+Li3PO4+8LiM2O4
[0050] Furthermore, when the activation treatment agent contains lithium carbonate, lithium may be consumed through the following reaction. LiPF6+4Li2CO3→ 6LiF+Li3PO4+4CO2
[0051] The separated solid component may be dried to remove the electrolyte washing solvent by reducing pressure and / or heating, if necessary. The heating temperature may be 50 to 200°C.
[0052] Step (1): Activation treatment agent mixing step Next, the prepared positive electrode mixture and an activation treatment agent containing one or more types of alkaline compounds are mixed to obtain a mixture.
[0053] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods. The order in which the positive electrode mixture and the activation treatment agent are mixed is not particularly limited.
[0054] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.
[0055] As a mixing method, dry mixing is preferred because mixing can be performed more easily. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.
[0056] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Corporation).
[0057] The activation treatment agent used in this step will be described in detail below.
[0058] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. The activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Here, potassium and / or sodium may be referred to as alkali metal element X. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or sodium compound.
[0059] When the activation treatment agent comes into contact with the positive electrode active material, the positive electrode active material can be activated. In particular, when the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the positive electrode active material is improved, and the activation of the positive electrode active material is further promoted.
[0060] In addition, the positive electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the positive electrode active material.
[0061] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target positive electrode active material, etc., and is usually 50 mass% or more, preferably 70 mass% or more, relative to the total mass of the activation treatment agent, and may be 100 mass% (an embodiment in which the activation treatment agent is essentially composed of alkali metal compounds).
[0062] The concentration of at least one alkali metal selected from the group consisting of potassium and sodium in the alkali metals contained in the alkali metal compound can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.
[0063] Examples of alkali metal compounds that are components of the activation treatment agent include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates, etc. These can be used alone or in combination as components of the activation treatment agent.
[0064] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0065] Here, in order to further enhance the activation effect of the positive electrode active material, the activation treatment agent may contain, in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds, the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.
[0066] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, the activation treatment agent preferably contains a lithium compound in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds. Suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.
[0067] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.
[0068] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and can be less than 50 mass% relative to the total mass of the activation treatment agent.
[0069] The amount of the activation treatment agent added in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the mass of the positive electrode active material contained in the positive electrode mixture.
[0070] When the activation treatment agent contains a potassium compound and a lithium compound, the ratio of the lithium content (molar) to the potassium content (molar) (lithium content / potassium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0071] When the activation treatment agent contains a sodium compound and a lithium compound, the ratio of the lithium content (molar basis) to the sodium content (molar basis) (lithium content / sodium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0072] When the activation treatment agent contains a potassium compound, the potassium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.
[0073] When the activation treatment agent contains a sodium compound, the sodium content (molar) contained in the activation treatment agent may be 1 to 200%, 10 to 200%, 50 to 200%, or 100 to 200%, 1% or more and less than 150%, 10% or more and less than 150%, 50% or more and less than 150%, or 100% or more and less than 150%, relative to the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0074] The number of moles of the alkali metal compound in the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent can be added so that the number of moles of the alkali metal element is 0.001 to 200 times the number of moles of the positive electrode active material (e.g., Formula A) contained in the positive electrode composite.
[0075] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material from the positive electrode mixture can be reduced, the oxidative decomposition rate of the carbon-based conductive material and the binder can be increased, the effect of preventing the generation of corrosive gas in the heating step can be improved, and the discharge capacity of the battery manufactured using the obtained positive electrode active material can be further increased.
[0076] At least one of the alkali metal compounds contained in the activation treatment agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."
[0077] By using an alkaline activation treatment agent, the generation of corrosive gas during the heating process can be further suppressed, so that the discharge capacity of the battery manufactured using the recovered positive electrode active material can be further increased. In addition, by using an alkaline activation treatment agent, the treatment speed of the carbon-based conductive material and the binder can be increased.
[0078] Examples of the alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in the alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals. Specifically, hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, and CsCO3; hydrogen carbonates such as LiHCO3, NaHCO3, KHCO3, RbHCO3, and CsHCO3; oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; and superoxides such as LiO2, NaO2, KO2, RbO2, and CsO2. One or more of these may be contained in the activation treatment agent.
[0079] In addition, when the conductive material contained in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the heating step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."
[0080] Use of an activation treatment agent having such oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the obtained positive electrode active material, and can also improve the effect of preventing the generation of corrosive gases during the heating process.
[0081] Examples of alkali metal compounds having the oxidizing power required to oxidize carbonaceous conductive materials and hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.
[0082] Specific examples include superoxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; LiO2, NaO2, KO2, RbO2, and CsO2; nitrates such as LiNO3, NaNO3, KNO3, RbNO3, and CsNO3; sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, and Cs2SO4; vanadates such as LiVO3, NaVO3, KVO3, RbVO3, and CsVO3; and molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, and CsMoO4.
[0083] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.
[0084] The alkali metal compound may be a carbonate or sulfate, or at least one selected from the group consisting of Li2CO3, Na2SO4, Na2CO3, and K2CO3, from the viewpoint of making it easier to make the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material.
[0085] Process (2): Heating process The heating step is a step of heating the mixture obtained in step (1) (hereinafter sometimes referred to as the "mixture before heating") to obtain a mixture after heating.
[0086] The mixture before heating may be heated to a temperature equal to or higher than the melting initiation temperature (Tmp) of the activation treatment agent, or may be heated to a temperature lower than the melting initiation temperature (Tmp) of the activation treatment agent.
[0087] "Melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase. The melting start temperature of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, when 5 mg of the mixture before heating is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), the melting start temperature is the temperature at which the DTA signal shows an endothermic peak.
[0088] The melting start temperature of the activation treatment agent is preferably 700° C. or lower, and more preferably 600° C. or lower. There is no lower limit to the melting start temperature of the activation treatment agent, but it may be, for example, 150° C. or higher.
[0089] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the positive electrode composite material and the activation treatment agent, the melting start temperature of the activation treatment agent becomes lower than the melting point of the activation treatment agent.
[0090] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10° C. / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting point of the activation treatment agent.
[0091] The atmosphere for heating is not particularly limited, and may be, for example, an oxygen-containing gas such as air, nitrogen, argon, or carbon dioxide. The pressure of the atmosphere is not particularly limited, and may be atmospheric pressure, a reduced pressure atmosphere, or a pressurized atmosphere.
[0092] Examples of the heating space include gas furnaces, electric furnaces, infrared heating furnaces, plasma heat treatment furnaces, heavy oil furnaces, light oil furnaces, hydrogen heat treatment furnaces, induction heating furnaces, vacuum furnaces, salt bath furnaces, tunnel furnaces, roller hearth kiln furnaces, rotary furnaces, walking beam furnaces, carbot furnaces, mesh belt furnaces, rotary kiln furnaces, shuttle kiln furnaces, and fluidized bed sintering furnaces. The heating space is a space in which the mixture to be heated is accommodated, and may be a closed space or an open space having an opening for carrying in or out the mixture. The heating space may be a batch furnace, a continuous furnace, or a fluidized furnace. For example, the rotary kiln furnace may be a batch type rotary kiln furnace or a continuous type rotary kiln furnace. When the heating space is a continuous furnace, the heating space may be a gas furnace, an electric furnace, an infrared heating furnace, a plasma heat treatment furnace, a heavy oil furnace, a light oil furnace, a hydrogen heat treatment furnace, an induction heating furnace, a walking beam furnace, a mesh belt furnace, a continuous rotary kiln furnace, or a continuous shuttle kiln furnace. The fluidized bed sintering furnace may be multi-stage, and the temperature may be changed in each stage.
[0093] The temperature in the heating step may be, for example, equal to or higher than the melting point of the activation treatment agent. The temperature in the heating step (maximum temperature in the heating space) may be, for example, 300 to 900°C, 300 to 700°C, or 300 to 600°C.
[0094] In step (2), the mixture before heating is heated to a temperature equal to or higher than the melting temperature of the activation treatment agent, which produces the following effects. That is, the activation treatment agent in a molten state comes into contact with the positive electrode active material, thereby suppressing deterioration of the crystal structure of the positive electrode active material. In addition, the activation treatment agent can also restore the crystal structure.
[0095] The contact of the molten activation treatment agent with the positive electrode active material can suppress deterioration of the crystal structure of the positive electrode active material, and in some cases can even restore the crystal structure.
[0096] When the molten activation treatment agent comes into contact with the carbon-based conductive material and binder, the rate of oxidative decomposition of the conductive material and binder is increased. Furthermore, when the molten activation treatment agent comes into contact with the binder and a fluorine compound derived from the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.
[0097] Furthermore, when the activation treatment agent contains the same alkali metal as the positive electrode active material, it is also possible to supply the alkali metal that is insufficient for the positive electrode active material.
[0098] The temperature of the heating step and the holding time at that temperature can be appropriately adjusted depending on the types and combinations of the positive electrode active material, conductive material, binder, alkali metal compound and other compounds contained in the activation treatment agent that constitute the positive electrode mixture. Usually, the temperature is in the range of 100 to 1500°C, and the holding time is about 10 minutes to 24 hours.
[0099] The temperature of the heating step is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each compound alone by mixing multiple types of compounds. When the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is the melting point of the alkali metal compound.
[0100] The temperature of the heating step may be, for example, lower than the melting start temperature of the activation treatment agent. In this specification, the temperature of the heating step being lower than the melting start temperature of the activation treatment agent means that the temperature of the heating step is maintained at a temperature lower than the melting start temperature of the activation treatment agent (heating is performed at a holding temperature lower than the melting start temperature of the activation treatment agent). In addition, the temperature of the heating step being lower than the melting start temperature of the activation treatment agent means that the temperature of the heating step is not set to a temperature equal to or higher than the melting start temperature of the activation treatment agent. The temperature of the heating step (maximum temperature in the heating space) may be, for example, 300 to 600°C, 350 to 575°C, or 400 to 550°C.
[0101] In step (2), the mixture before heating is heated to a temperature below the melting temperature of the activation treatment agent, thereby suppressing deterioration of the crystal structure of the positive electrode active material caused by heating at high temperatures, and making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material. In addition, the crystal structure can be restored by heating the mixture before heating together with the activation treatment agent.
[0102] The heated activation treatment agent comes into contact with the carbon-based conductive material and binder, thereby increasing the rate of oxidative decomposition of the conductive material and binder. Furthermore, the heated activation treatment agent comes into contact with the binder and a fluorine compound derived from the electrolyte, thereby stabilizing the fluorine component as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.
[0103] After the heating step, the mixture can be cooled to any temperature, such as about room temperature, as necessary. In this manner, a heated mixture containing a heated positive electrode active material is obtained.
[0104] Step (3): First washing step The first water-washing step is a step of contacting the heated mixture with a first liquid containing water and an alkali metal compound after the heating step of step (2) to obtain a first solid component and a first liquid component.
[0105] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (such as alkali metal compounds), undecomposed conductive material and binder, and other undecomposed materials of the positive electrode mixture. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte. In the first water washing step, it is preferable to remove components derived from the activation treatment agent (such as alkali metal compounds), unreacted activation treatment agent, undecomposed conductive material and binder, and other undecomposed materials of the positive electrode mixture, from the viewpoint of more easily achieving rate characteristics equivalent to those of a battery manufactured using an unused positive electrode active material by increasing the purity of the positive electrode active material.
[0106] Examples of the alkali metal compound contained in the first liquid include hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, tungstates, etc. The first liquid may contain one or more types of alkali metal compounds.
[0107] Specific examples of the alkali metal compound contained in the first liquid include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0108] The alkali metal compound contained in the first liquid may be derived from the activation treatment agent. For example, the first liquid may contain at least a part of the waste liquid generated after washing the mixture after heating. That is, the first liquid may be a reused waste liquid generated after washing the mixture after heating. For example, at least a part of the second liquid component generated in the second water washing step described below may be reused and used as the first liquid. By using the waste liquid generated after washing the mixture after heating, it is possible to reduce the amount of waste water generated by water washing when water washing is performed multiple times.
[0109] The amount of water in the first liquid may be 50% by mass or more. The pH of the first liquid may be adjusted by adding a component other than water and an alkali metal compound to the first liquid in order to increase the solubility of the water-soluble components or to increase the processing speed. For example, the first liquid may contain ammonia as an alkali.
[0110] The first water-washing step may involve, for example, contacting the heated mixture with a first liquid to obtain a first slurry, and then subjecting the first slurry to solid-liquid separation to obtain a first solid component and a first liquid component.
[0111] In the first water washing step, the heated mixture may be mixed with a first liquid and then stirred to obtain a first slurry. This promotes dissolution of the water-soluble components. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.
[0112] The first slurry is separated into a first liquid component and a first solid component by solid-liquid separation of the first slurry. The method for solid-liquid separation of the first slurry may be a conventionally known method, for example, filtration or centrifugation.
[0113] The first solid component mainly contains a positive electrode active material. The first liquid component contains a water-soluble component other than the positive electrode active material. The first liquid component contains an alkali metal compound, a binder, a fluorine component derived from the electrolyte, and the like.
[0114] The amount of the first liquid to be brought into contact with the mixture after heating is appropriately determined taking into consideration the amounts of the positive electrode active material and water-soluble components other than the positive electrode active material contained in the mixture after heating.
[0115] Step (4): Second washing step The second water-washing step is a step of contacting the first solid component with a second liquid that contains water and has a smaller content of alkali metal compounds than the first liquid, and then obtaining a second solid component and a second liquid component.
[0116] In addition to the positive electrode active material, the first solid component may contain components (such as alkali metal compounds) derived from the activation treatment agent that were not completely removed in the first water-washing step, and fluorine components derived from the electrolyte. In the second water-washing step, undecomposed conductive material and binder remaining in the first solid component, other undecomposed substances of the positive electrode mixture, and fluorine components derived from the electrolyte are further removed.
[0117] The second liquid contains at least water. The second liquid has a lower content of alkali metal compounds than the first liquid. The second liquid may have a content of alkali metal compounds of 0% by mass (an embodiment in which the second liquid contains substantially no alkali metal compounds).
[0118] When the second liquid contains an alkali metal compound, examples of the alkali metal compound contained in the second liquid include hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, tungstates, etc. The second liquid may contain one or more types of alkali metal compounds.
[0119] Specific examples of the alkali metal compound contained in the second liquid include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0120] The alkali metal compound contained in the second liquid may be derived from the activation treatment agent. For example, the second liquid may contain at least a part of the waste liquid generated after washing the mixture after heating. In other words, the second liquid may be a reused waste liquid generated after washing the mixture after heating. For example, the second liquid may contain at least a part of the components of the first liquid. This makes it possible to reduce the amount of waste water generated by washing when washing with water is performed multiple times.
[0121] The amount of water in the second liquid may be 50% by mass or more. The pH of the second liquid may be adjusted by adding a component other than water and an alkali metal compound to the second liquid in order to increase the solubility of the water-soluble components or to increase the processing speed. For example, the second liquid may contain ammonia as an alkali.
[0122] The second liquid may be less than the first liquid. For example, the amount of the second liquid may be 90% or less, 80% or less, 70% or less, or 60% or less of the first liquid. The smaller the amount of the second liquid, the more the amount of wastewater can be reduced.
[0123] The second water-washing step may, for example, involve contacting the first solid component with a second liquid to obtain a second slurry, and then subjecting the second slurry to solid-liquid separation to obtain the second solid component and the second liquid component. In addition, when the first solid component and the first liquid component are obtained by filtering the first slurry in the first water-washing step, the second water-washing step may involve contacting the first solid component after filtration (the first solid component present as a cake on the filter paper) with the second liquid to wash the first solid component without forming a slurry, thereby obtaining the second solid component and the second liquid component.
[0124] In the second washing step, when the second slurry is obtained, the first solid component and the second liquid may be mixed and then stirred to obtain the second slurry. This promotes dissolution of the water-soluble component. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.
[0125] In the second water washing step, when the second slurry is obtained, the second slurry is separated into a second liquid component and a second solid component by solid-liquid separation of the second slurry. The method for solid-liquid separation of the second slurry may be a conventionally known method, for example, filtration or centrifugation.
[0126] The second solid component mainly contains a positive electrode active material. The second liquid component contains a water-soluble component other than the positive electrode active material. The second liquid component contains an alkali metal compound, a binder, a fluorine component derived from the electrolyte, and the like. The content of the alkali metal compound in the second liquid component may be smaller than the content of the alkali metal compound in the first liquid component.
[0127] The amount of the second liquid to be brought into contact with the first solid component is appropriately determined taking into consideration the amounts of the positive electrode active material and the water-soluble component other than the positive electrode active material contained in the second solid component.
[0128] Step (5): Positive electrode active material recovery step The positive electrode active material recovery step is a step of recovering a recycled positive electrode active material from the second solid component after the second water-washing step of step (4).
[0129] After the second water-washing step, further water washing may be performed to further remove components derived from the activation treatment agent, fluorine components derived from the electrolyte, etc. In other words, the positive electrode active material recovery step may include a third, fourth, fifth, ..., nth water-washing step (n is an integer of 3 or more).
[0130] The positive electrode active material recovery step may include, for example, a step of exposing the second solid component to a heated and / or reduced pressure environment to remove water from the second solid component (drying step). When further water washing is performed after the second water washing step, the drying step is a step of exposing the solid component obtained after the final water washing step to a heated and / or reduced pressure environment to remove water from the solid component.
[0131] In the drying step, the heating temperature is preferably 100°C or higher in order to remove water. It is more preferably 150°C or higher in order to thoroughly remove water. In particular, a temperature of 250°C or higher is preferable because it further increases the discharge capacity of a battery manufactured using the obtained positive electrode active material. The temperature in the drying step may be constant, or may be changed stepwise or continuously. The heating temperature range may be, for example, 10°C or higher and less than 900°C.
[0132] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It can be Pa.
[0133] The positive electrode active material recovery step may include, for example, a step of heat-treating the second solid component (annealing step). In the case where the activation treatment agent is heated to a melting initiation temperature or higher and the positive electrode active material recovery step includes a drying step, the annealing step may be, for example, a step of heat-treating the dried solid component at less than 900°C.
[0134] In the case where the activation treatment agent is heated at a temperature lower than the melting initiation temperature and the positive electrode active material recovery step includes a drying step, the annealing step may be, for example, a step of heating the dried solid component at a temperature higher than that of step (2). In this case, the temperature at which the dried solid component is heated may be higher than 700°C, 750°C or higher, 800°C or higher, 850°C or higher, or 900°C or higher from the viewpoint of vaporizing components other than the positive electrode active material and removing impurities, and from the viewpoint of making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material by sufficiently increasing the crystallite size of the positive electrode active material.
[0135] In the annealing step, the atmosphere for the heat treatment is not particularly limited, but it is preferable that the heat treatment is performed in an oxygen-containing atmosphere such as air. The heat treatment temperature can be 100° C. or higher. The heat treatment holding time can be 1 minute to 24 hours. In particular, it is preferable to heat the material at a temperature of 350° C. or higher for 0.1 to 5 hours.
[0136] [Second embodiment] The method for producing a recycled positive electrode active material according to the second embodiment of the present invention includes the following steps: Note that, to the extent technically possible, the description of the first embodiment can be appropriately applied to the second embodiment. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to obtain a heated mixture Step (3): A step of contacting the heated mixture with a first liquid containing water, and then obtaining a first solid component and a first liquid component. Step (4): contacting the first solid component with a second liquid containing water and at least a portion of the first liquid component, and then obtaining a second solid component and a second liquid component. Step (5): Recovering recycled positive electrode active material from the second solid component
[0137] The method for producing a recycled positive electrode active material according to the second embodiment also makes it possible to reduce the amount of wastewater generated by washing with water when washing with water is performed multiple times. In the method for producing a recycled positive electrode active material according to the second embodiment, a liquid containing at least a part of the first liquid component generated in the first washing with water is used as the liquid for the second washing with water. Although the waste liquid (first liquid component) generated in the first washing with water contains an alkali metal compound derived from the activation treatment agent, the alkali metal compound in the first liquid is less than the saturated concentration. Therefore, even if the first liquid component is used as the liquid for the second washing with water, the liquid for the second washing with water can dissolve the alkali metal compound derived from the activation treatment agent (especially, fluorides such as sodium and potassium, and easily soluble alkali metal compounds such as carbonates), etc., and therefore it is possible to remove the alkali metal compound derived from the activation treatment agent in the same way as in the conventional washing method using pure water, etc. Therefore, by reusing the first liquid component as the second liquid, it is possible to reduce the amount of wastewater while removing the alkali metal compound derived from the activation treatment agent in the same way as in the conventional method.
[0138] [Third embodiment] The method for producing a recycled positive electrode active material according to the third embodiment of the present invention includes the following steps: Note that, to the extent technically possible, the description of the first embodiment can be appropriately applied to the third embodiment. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to obtain a heated mixture Step (3): A step of contacting the heated mixture with a first liquid containing water, and then obtaining a first solid component and a first liquid component. Step (4): contacting the first solid component with a second liquid that contains water and is in an amount less than the first liquid, and then obtaining a second solid component and a second liquid component. Step (5): Recovering recycled positive electrode active material from the second solid component
[0139] The method for producing a recycled positive electrode active material according to the third embodiment also makes it possible to reduce the amount of wastewater generated by washing with water when washing with water is performed multiple times. In the method for producing a recycled positive electrode active material according to the third embodiment, the liquid (second liquid) used in the second washing with water is less than the liquid (first liquid) used in the first washing with water. According to the study by the present inventors, even if the second liquid is less than the first liquid, most of the components derived from the activation treatment agent and the fluorine components derived from the electrolyte can be removed by the first washing with water, so that even if the second liquid is small, it is possible to sufficiently remove the components derived from the remaining activation treatment agent and the fluorine components derived from the electrolyte. Therefore, when producing a recycled positive electrode active material, by making the second liquid less than the first liquid, it is possible to reduce the amount of wastewater while removing the undecomposed conductive material and the fluorine components derived from the electrolyte in the same manner as in the conventional method.
[0140] The recycled positive electrode active material obtained from the battery mixture by using the manufacturing method of the recycled positive electrode active material according to each embodiment of the present invention can be reused in the same way as unused active material. Methods for manufacturing positive electrodes and batteries using recycled positive electrode active materials are well known.
[0141] The final discharge capacity of the recycled positive electrode active material according to each embodiment of the present invention can be 150 mAh / g or more. EXAMPLES
[0142] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0143] Measurement of the physical properties of the positive electrode active material and the recycled positive electrode active material, and a charge / discharge test using a battery using the positive electrode active material were carried out as follows.
[0144] [Element content] The content of alkali metal elements in the solution and the powder was analyzed using an ICP emission spectrometer (e.g., SPS3000 manufactured by SII NanoTechnology Inc.) for the solution and the acid solution in which the powder was dissolved.
[0145] (Reference example 1) <Production of positive electrodes> The positive electrode described below was prepared by the following procedure. A mixture was obtained by mixing 92 parts by mass of a positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by mass of PVdF (binder, manufactured by Kureha Corporation, product number: #1100), and 5 parts by mass of acetylene black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. The mixture was kneaded with a rotation-revolution type mixer (ARE-310 manufactured by Thinky Corporation) to prepare a positive electrode mixture paste. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 50% by mass.
[0146] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 3.0 ± 0.1 mg / cm2. 2 The positive electrode composite paste was applied so that the positive electrode was formed as follows: After that, it was vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of this positive electrode was 1.65 cm 2 It was decided.
[0147] <Battery manufacturing> The coin-type battery described below was produced by the following procedure. The above-mentioned positive electrode, electrolyte, separator, and negative electrode were combined to produce a nonaqueous electrolyte secondary battery (coin-type battery). The battery was assembled in a glove box in an argon atmosphere. As the electrolyte, a solution in which LiPF6 was dissolved at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was used. As the separator, a laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used, and metallic lithium was used as the negative electrode.
[0148] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.07 Ni 0.47 Mn 0.48 Fe 0.05 A positive electrode active material having a crystal structure of R-3m and a molecular weight of 02 was prepared. The above-mentioned coin-type battery was produced using this positive electrode active material (unused positive electrode active material), and the following charge-discharge test (rate test) was carried out while maintaining the temperature at 25°C. The 0.2C discharge capacity was 138mAh / g, and the 5C discharge capacity was 106mAh / g. The larger the 0.2C discharge capacity, the higher the rated capacity obtained, and the larger the 5C discharge capacity, the higher the output characteristics obtained. (conditions) Maximum charging voltage: 4.3V Charging current: 0.2mA / cm 2 Charging time: 8 hours Minimum discharge voltage: 2.5V 0.2C discharge current: 0.2mA / cm 2 5C discharge current: 5.0mA / cm 2
[0149] The electrode mixture was mechanically scraped off from the positive electrode used in the above battery, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was mixed with 0.1 mol of K2CO3 per 1 mol of positive electrode active material and 0.1 mol of Na2CO3 per 1 mol of positive electrode active material as an activation treatment agent to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 700°C.
[0150] The mixture before heating was placed in an electric furnace and heated in an air atmosphere under conditions of a heating temperature of 700° C. (above the melting start temperature of the activation treatment agent) and a heating time of 240 minutes.
[0151] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and a charge / discharge test was performed under the above conditions while maintaining the temperature at 25°C. The 0.2C discharge capacity was 135mAh / g, and the 5C discharge capacity was 94mAh / g, which was comparable to the discharge capacity of a coin-type battery produced using an unused positive electrode active material.
[0152] (Reference example 2) <Production of positive electrodes before recycling> The positive electrode active material has the composition LiNi 0.33 Co 0.33 Mn 0.33 A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. When the above coin-type battery was produced using this positive electrode active material (unused positive electrode active material), the initial charge capacity was 178.3mAh / g and the initial discharge capacity (0.2C) was 163.4mAh / g. In addition, when the following charge / discharge test (rate test) was performed while maintaining the temperature at 25°C, the 0.2C discharge capacity was 163.1mAh / g and the 5C discharge capacity was 141.3mAh / g.
[0153] The electrode mixture was mechanically scraped off from the cathode of the process waste material generated during the preparation of the above cathode, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the cathode was mixed with 0.1 mol of Li2CO3 per 1 mol of the cathode active material and 0.1 mol of Na2SO4 per 1 mol of the cathode active material as activation treatment agents to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 510°C.
[0154] 30 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300° C. / h, a heating temperature of 450° C. (lower than the melting start temperature of the activation treatment agent), and a heating time of 360 minutes.
[0155] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried by suction at 100°C for 1 hour.
[0156] The solid component after drying was placed in an electric furnace, and heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material after heating. Next, the recycled positive electrode active material after heating was naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. When the above coin-type battery was produced using the recycled positive electrode active material, the initial charge capacity was 180.5mAh / g and the initial discharge capacity was 161.1mAh / g. In addition, when the initial charge / discharge (rate test) was performed under the above conditions while maintaining at 25°C, the 0.2C discharge capacity was 160.2mAh / g and the 5C discharge capacity was 133.9mAh / g.
[0157] Comparative Example 1 A pre-heated mixture is obtained in the same manner as in Reference Example 1. The mixture is placed in an alumina firing container and placed in an electric furnace, and the mixture is heated under the following conditions: a temperature increase rate of 200°C / hour, a heating temperature of 700°C (above the melting start temperature of the activation treatment agent), and a heating time of 240 minutes. The heated mixture is naturally cooled to room temperature, and then the heated mixture is collected.
[0158] The heated mixture is pulverized, and distilled water A1 is added and stirred to obtain slurry A. The obtained slurry A is subjected to suction filtration to separate into a cake on the filter paper (solid component A1) and a filtrate (liquid component A1). Distilled water A2 in an amount equal to the distilled water A1 is added to the cake on the filter paper (solid component A1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component A2) and a filtrate (liquid component A2). Both liquid components A1 and A2 contain K2CO3 and Na2CO3.
[0159] The cake on the filter paper (solid component A2) is collected and dried at 300°C for 6 hours to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material), and the 0.2C and 5C discharge capacities measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material).
[0160] Example 1 The heated mixture is pulverized in the same manner as in Comparative Example 1. The pulverized heated mixture is mixed with the same amount of liquid component A2 as the distilled water A1 in Comparative Example 1 to obtain a slurry B. The obtained slurry B is subjected to suction filtration to separate into a cake on the filter paper (solid component B1) and a filtrate (liquid component B1). Distilled water B2 in the same amount as the liquid component A2 is added to the cake on the filter paper (solid component B1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component B2) and a filtrate (liquid component B2).
[0161] The cake on the filter paper (solid component B2) is collected and dried at 300°C for 6 hours to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material (unused active material) before recycling. The discharge capacity measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material (unused active material) before recycling.
[0162] Example 2 The heated mixture is pulverized in the same manner as in Comparative Example 1. The pulverized heated mixture is mixed with distilled water C1 in the same amount as the distilled water A1 in Comparative Example 1 to obtain slurry C. The obtained slurry C is subjected to suction filtration to separate into a cake on the filter paper (solid component C1) and a filtrate (liquid component C1). A mixture of distilled water and liquid component C1 (distilled water:liquid component = 1:1 (volume ratio)) is added to the cake on the filter paper (solid component C1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component C2) and a filtrate (liquid component C2).
[0163] The cake on the filter paper (solid component C2) is collected and dried at 300°C for 6 hours to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material). The discharge capacity measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material before recycling (unused active material).
[0164] Example 3 The heated mixture is pulverized in the same manner as in Comparative Example 1. The pulverized heated mixture is mixed with distilled water D1 in the same amount as the distilled water A1 in Comparative Example 1 to obtain a slurry D. The obtained slurry D is subjected to suction filtration to separate into a cake on the filter paper (solid component D1) and a filtrate (liquid component D1). Distilled water D2 is poured into the cake on the filter paper (solid component D1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component D2) and a filtrate (liquid component D2). The amount of distilled water D2 is made less than the amount of distilled water D1.
[0165] The cake on the filter paper (solid component D2) is collected and dried at 300°C for 6 hours to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material (unused active material) before recycling. The discharge capacity measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material (unused active material) before recycling.
[0166] Comparative Example 2 A pre-heated mixture is obtained in the same manner as in Reference Example 2. The mixture is placed in an alumina firing container and placed in an electric furnace, where it is heated at a heating rate of 300°C / hour, at a heating temperature of 450°C (lower than the melting start temperature of the activation treatment agent), and for a heating time of 360 minutes. The heated mixture is naturally cooled to room temperature, and then the heated mixture is collected.
[0167] The heated mixture is pulverized, and distilled water E1 is added and stirred to obtain slurry E. The obtained slurry E is subjected to suction filtration to separate into a cake on the filter paper (solid component E1) and a filtrate (liquid component E1). Distilled water E2 in an amount equal to the distilled water E1 is added to the cake on the filter paper (solid component E1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component E2) and a filtrate (liquid component E2). Both liquid components E1 and E2 contain Li2CO3 and Na2SO4.
[0168] The cake on the filter paper (solid component E2) is collected and dried at 300°C for 6 hours, and then the solid component E2 is heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material), and the 0.2C and 5C discharge capacities measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material).
[0169] Example 4 The heated mixture is pulverized in the same manner as in Comparative Example 2. The pulverized heated mixture is mixed with the same amount of liquid component E2 as the distilled water E1 in Comparative Example 2 to obtain a slurry F. The obtained slurry F is subjected to suction filtration to separate into a cake on the filter paper (solid component F1) and a filtrate (liquid component F1). Distilled water F2 in the same amount as the liquid component E2 is added to the cake on the filter paper (solid component F1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component F2) and a filtrate (liquid component F2).
[0170] The cake on the filter paper (solid component F2) is collected and dried at 300°C for 6 hours, and then the solid component F2 is heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material (unused active material) before recycling. The discharge capacity measured in a charge / discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material (unused active material) before recycling.
[0171] Example 5 The heated mixture is pulverized in the same manner as in Comparative Example 2. The pulverized heated mixture is mixed with the same amount of distilled water G1 as the distilled water E1 in Comparative Example 2 to obtain a slurry G. The obtained slurry G is subjected to suction filtration to separate into a cake on the filter paper (solid component G1) and a filtrate (liquid component G1). A mixture of distilled water and liquid component G1 (distilled water:liquid component = 1:1 (volume ratio)) is added to the cake on the filter paper (solid component G1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component G2) and a filtrate (liquid component G2).
[0172] The cake on the filter paper (solid component G2) is collected and dried at 300°C for 6 hours, and then the solid component G2 is heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material (unused active material) before recycling. The discharge capacity measured in a charge / discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material (unused active material) before recycling.
[0173] Example 6 The heated mixture is pulverized in the same manner as in Comparative Example 2. The pulverized heated mixture is mixed with distilled water H1 in the same amount as the distilled water E1 in Comparative Example 1 to obtain a slurry H. The obtained slurry H is subjected to suction filtration to separate a cake on the filter paper (solid component H1) and a filtrate (liquid component H1). Distilled water H2 is poured into the cake on the filter paper (solid component H1), and then suction filtration is performed again to obtain a cake on the filter paper (solid component H2) and a filtrate (liquid component H2). The amount of distilled water H2 is made less than the amount of distilled water H1.
[0174] The cake on the filter paper (solid component H2) is collected and dried at 300°C for 6 hours, and then the solid component H2 is heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the resulting recycled positive electrode active material are comparable to those of the positive electrode active material (unused active material) before recycling. The discharge capacity measured in a charge / discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material (unused active material) before recycling.
[0175] In Example 1, the wastewater from Comparative Example 1 is reused to wash the mixture after heating, and in Example 4, the wastewater from Comparative Example 2 is reused to wash the mixture after heating, so that the amount of wastewater can be reduced in the process for producing a recycled positive electrode active material, compared to the case where distilled water is used for washing.
[0176] In Examples 2 and 5, the amount of wastewater generated during the production of recycled positive electrode active materials can be reduced by reusing the wastewater (filtrate) generated when washing the mixture after heating.
[0177] In Examples 3 and 6, the amount of distilled water D2, H2 used in the second water washing is made smaller than the amount of distilled water D1, H1 used in the first water washing, thereby making it possible to reduce the amount of wastewater generated during the production of recycled positive electrode active material.
Claims
1. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture to obtain a heated mixture. (3) contacting the mixture after heating with a first liquid containing water and an alkali metal compound, and then obtaining a first solid component and a first liquid component; The first liquid is obtained by heating a mixture containing a positive electrode mixture including a positive electrode active material and an activation treatment agent including one or more alkali metal compounds, and contains at least a part of a waste liquid generated after washing the heated mixture with water other than the heated mixture. (4) contacting the first solid component with a second liquid that contains water and has a lower content of alkali metal compounds than the first liquid, and then obtaining a second solid component and a second liquid component. (5) A step of recovering a recycled positive electrode active material from the second solid component.
2. The method of claim 1 , wherein the second liquid comprises at least a portion of the first liquid component.
3. The method of claim 1 , wherein the second liquid is less than the first liquid.
4. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture to obtain a heated mixture. (3) contacting the mixture after heating with a first liquid containing water, and then obtaining a first solid component and a first liquid component; (4) contacting the first solid component with a second liquid containing water and at least a portion of the first liquid component, and then obtaining a second solid component and a second liquid component; (5) A step of recovering a recycled positive electrode active material from the second solid component.
5. The method of claim 4 , wherein the second liquid is in a smaller amount than the first liquid.
6. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture to obtain a heated mixture. (3) contacting the mixture after heating with a first liquid containing water, and then obtaining a first solid component and a first liquid component; (4) contacting the first solid component with a second liquid that contains water and is less in amount than the first liquid, and then obtaining a second solid component and a second liquid component; (5) A step of recovering a recycled positive electrode active material from the second solid component.
7. The method according to any one of claims 1 to 6, wherein in the step (2), the mixture is heated to a temperature equal to or higher than a melting start temperature of the activation treatment agent.
8. The method according to any one of claims 1 to 6, wherein in the step (2), the mixture is heated to a temperature lower than a melting initiation temperature of the activation treatment agent.
Citation Information
Patent Citations
Method for recovering active material from discarded battery material
JP2012186150A
Positive electrode active material recovery method
JP2015185471A
Lithium recovery method
JP2020132951A
Separation method for cobalt and nickel
JP2023150694A
Processing of cobaltous sulphate / dithionate liquors derived from cobalt resource
JP2023159399A